Postulat Entitas: Landasan Teori Akuntansi, Penerapan dalam Struktur Laporan Keuangan, dan Implikasi Bisnis - Olive Ondita Sibarani; Sulastri Ladyana Samosir; Riska Harianingsih; Erik Martua Simatupang; Arif Anakampun; Jufri Darma (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
The entity postulate (economic/entity assumption) is a fundamental principle in accounting that requires a company’s economic activities to be strictly separated from those of its owners, affiliates, or unrelated external parties. This paper aims to examine the theoretical foundations of the entity postulate, differentiate it from the concept of a legal entity, and analyze its application within modern financial reporting structures based on IFRS and FASB standards. The study employs a descriptive qualitative approach by reviewing primary literature including the Conceptual Framework for Financial Reporting (IFRS Foundation), the Accounting Standards Codification (FASB), and recent empirical studies. The findings indicate that the entity postulate plays an essential role in ensuring accountability, transparency, and reliability in financial reporting, while also influencing governance, regulatory compliance, valuation accuracy, and the mitigation of manipulation risks. The study concludes that although the entity postulate significantly strengthens the quality of financial reporting, its practical implementation still faces notable challenges across various business contexts